2017
DOI: 10.4103/2347-5625.199077
|View full text |Cite
|
Sign up to set email alerts
|

Caring for patients with advanced breast cancer: The experiences of Zambian nurses

Abstract: Objective:The objective of this study was to describe the experiences of Zambian nurses caring for women with advanced breast cancer.Methods:We used a qualitative descriptive design and purposive sampling. Seventeen in-depth interviews were conducted with registered nurses practicing in the Cancer Diseases Hospital and the University Teaching Hospital, Lusaka, Zambia, and analyzed using thematic analyses.Results:Two themes emerged from the data - caring for women with advanced breast cancer is challenging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…Whether these perceptions influenced the behaviour of our participants' friends and communities is debatable as knowledge of cancer in the South African population is generally poor (Maree & Wright, 2010;Maree, Wright, & Makua, 2011) and might not enable people to judge who contributed to their cancer. Irrespective of the knowledge and perceptions underpinning stigmatisation, it is a reality for cancer patients living in Africa (Maree & Kaila, 2014;Maree & Mulonda, 2017), causing psychosocial problems and loss of employment, rendering some unable to care for their families. Most of our participants did not complete secondary education, which could have played a role in being unemployed.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these perceptions influenced the behaviour of our participants' friends and communities is debatable as knowledge of cancer in the South African population is generally poor (Maree & Wright, 2010;Maree, Wright, & Makua, 2011) and might not enable people to judge who contributed to their cancer. Irrespective of the knowledge and perceptions underpinning stigmatisation, it is a reality for cancer patients living in Africa (Maree & Kaila, 2014;Maree & Mulonda, 2017), causing psychosocial problems and loss of employment, rendering some unable to care for their families. Most of our participants did not complete secondary education, which could have played a role in being unemployed.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses, especially those without any specialized oncology training, often feel inadequate in meeting the challenge of cancer care due to a lack of competence, education, and skills (Araújo et al, 2015). Studies also reported that shortage of adequately trained oncology experts has led to limitations in capacity and the quality of care provided (Maree et al, 2017) as many nurses report that they did not receive any education or training in palliative care during both their academic education and in the clinical setting (Hassankhani et al, 2020). Nurses in cancer care wards offer care for the entire course of management of patients with cancer and assist in a peaceful death, (Al zoubi et al, 2019).…”
Section: Nurses' Perceived Challenges In the Management Of Hospitaliz...mentioning
confidence: 99%
“…Outra pesquisa realizada com enfermeiras zambianas também revelou que a ausência de formação oncológica contribui para experiências negativas e impedem a prestação de cuidados de Enfermagem ideal, preocupação existente em países desenvolvidos e em desenvolvimento, o que evidencia a necessidade de capacitar esses profissionais para o atendimento a pacientes oncológicos (9) . Diante desse contexto, surgiu a necessidade de realizar esta pesquisa, a qual teve como pergunta norteadora: Qual a percepção dos enfermeiros sobre o cuidado a pacientes oncológicos na APS?…”
Section: Introductionunclassified